In-between spaces in the Levant: Conceptual reflections. Issue 3 (26th May 2020) - Meier, Daniel
ABSTRACT: In-between border spaces are numerous in the Levant region and are usually of two types: those resulting into buffer zones as a result of demilitarized spaces and those turning as a region under the occupation of a foreign state. But there is a lack of clear theoretical and analytical framework as they stayed somehow understudied territories and spaces that are generally located at the edges of the states and thus are poorly documented and sometimes can even be described as hidden geographies. This introduction explores three key concepts – space, power, and identity – as they provide three directions of investigation that are interlinked in this problem: the territoriality, the political power, and the issue of the relationship between the Self and the Others. Therefore, the general questioning aims at understanding whatÂ are the reasons for the appearance, the existence, and the persistence of in-between border spaces. The paper provides with various tools in several disciplines in order to shape and suggest ways of delineating the issue of in-between spaces in border regions.